Self-Efficacy and Anxiety in Facing School Exams - Aini, Nur; Wahyuni, Nengsih Sri; Ardiansyah, Fuad (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Researchers found a problem faced by junior high school students, namely feeling unable to face computer-based exams, which can trigger feelings of anxiety. This quantitative correlational research aims to determine the relationship between self-efficacy and anxiety in junior high students when facing school exams. In this study, researchers used a purposive sampling technique with a totalof 251 junior high school students who were taking school exams and came from sorong district. The research instrument used a self-efficacy scale and an anxiety scale. This research uses two scales, namely the self-efficacy scale and the anxiety scale. The research results showed that there was a correlation of r = -0.181 and a significance value of 0.004 (p<0.05), which means there is a relationship between self-efficacy and anxiety in the remaining junior high school students in facing school exams. The higher the self-efficacy, the lower the anxiety. Conversely, the lower self-efficacy, the higher the anxiety. The results of this research can serve as a reference and provide insight for students in facing school exams to increase their sel-efficacy to minimize the anxiety that junior high school students have in facing school exams.Peneliti menemukan suatu permasalahan yang di hadapi pada siswa SMP yaitu merasa ketidakmampuan dalam menghadapi ujian berbasis komputer sehingga dapat memicu timbulnny perasaan cemas. Penelitian kuanitatif korelasional ini bertujuan untuk mengetahui hubungan antara efikasi diri dengan kecemasan pada siswa SMP dalam menghadapi Ujian Sekolah. Pada penelitian ini, peneliti menggunakan teknik purposive sampling dengan total partisipan sebanyak 251 siswa SMP yang sedang dalam menghadapi ujian sekolah dan berasal dari kabupaten sorong. Instrumen penelitian menggunakan skala efikasi diri dan skala kecemasan. Penelitian ini menggunakan dua skala yaitu skala efikasi diri dan skala kecemasan. Hasil penelitian menunjukkan adanya korelasi sebesar r = -0.181 dan nilai signifikansi sebesar 0,004 (p<0,05) yang berarti ada hubungan efikasi diri dengan kecemasan pada siswa SMP dalam menghadapi ujian sekolah. Makin tinggi efikasi diri maka semakin rendah kecemasannya. Sebaliknya semakin rendah efikasi diri maka semakin tinggi kecemasannya. Hasil dari penelitian ini bisa menjadi acuan dan memberikan wawasan untuk para siswa dalam menghadapi ujian sekolah agar dapat meningkatkan efikasi diri nya sehingga dapat meminimalisir kecemasan yang dimiliki siswa SMP dalam menghadapi ujian sekolah.